The most common etiological agents of prosthetic joint infections in orthopaedics - Jozef Breznicky; Martin Novak (Medicinski glasnik, 2019)
Aim: To determine the spectrum of causative agent of prosthetic joint infections in orthopaedics. Methods: In the group of 50 patients with periprosthetic infection the results of microbiological analysis of minimally two samples gained intraoperatively were analysed. Results: The only pathogen in the group of acute infection was Staphylococcus (S.) aureus. In case of delayed infection the most frequent pathogen was also S. aureus and in case of late infection it was coagulase-negative staphylococcus. Conclusion: A better understanding of the most common agents responsible for prosthetic joint infection helps us to properly prepare the patient (by eradicating of potential focus) with adequate antibiotic prophylaxis and early treatment of suspected infections to further reduce the incidence of infectious complications in orthopaedics. It is important to bear in mind that patients who have undergone total joint replacement have a risk of infection for the rest of their lives.
Keywords: coagulase-negative staphylococcus; Staphylococcus aureus; total joint replacement